Grenzen des medizinischen Fortschritts aus ethischer Sicht - Huber, Wolfgang (Zeitschrift für evangelische Ethik, 1994)
When discussing the Iimits of medical progress from an ethical point of view, medical progress must neither be glorified nor rejected. Ethical reflection rather has to consider the different kinds of Iimits of medical practice and research. Starting from an ethics of dignity, that refuses to define human being and dignity only by the fact of human cerebration, the article argues for extending the Iimits of medicine in order to fight against the epidemics, and for correcting new Iimits of medical care, that result from the over specialisation of medical technics and the division of medical labour. Above all however medical treatment has to respect those Iimits, that are given by the dignity of the individual. Therefore for example the criteria for organ transplantation must be very strict in order to avoid any commercialization of donating organs, and in order to respect the process of human death.